Successful Cascade of Care and Cure HCV in 5382 Drugs Users: How Increase HCV Treatment by Outreach Care, Since Screening to Treatment - Remy, Andre-Jean; Bouchkira, Hakim; Hervet, Jeremy; Happiette, Arnaud; Wenger, Hugues (Journal of Digestive Disorders And Diagnosis, 2019)
Introduction In France 33% of patients didn’t take care of hepatitis C because there were no diagnosed. Drug injection was main contamination route of hepatitis C virus (HCV) in France. French guidelines were to treat all inmates and drug users, even fibrosis level. Access of HCV screening, care and treatment in drugs users, prisoners and homeless was low in France. They were considered as difficult to treat populations. All these patients need specific support. Hepatitis Mobile Team (HMT) was created in July 2013 to increase screening care and treatment of hepatitis B and C patients. HMT was composed of hepatologist, nurses, social workers and health care worker. Objective increase outreach screening care treatment access and cure of our target population. Patients and methods Target population was drugs users, prisoners, homeless, precarious people, migrants and psychiatric patients. We proposed part or all of our services to our 42 medical and social partners: HCV HBV screening by DBS (dried blood test); outside DBS and FIBROSCAN in converted van; Outreach open center; Drug users information and prevention, Free blood tests in primary care;, Staff training; Social screening and diagnosis; Mobile liver stiffness Fibroscan in site; Advanced on-site specialist consultation; Easy access to pre-treatment commission; Low cost mobile phones for patients; Individual psycho-educative intervention sessions; Collective educative workshops; Peer to peer educational program; Specific one day hospitalizations. All services were free for patients and for partners. Results from 2013 July to 2018 December, we did 8382 DBS for 5382 people (3053 HCV DBS) and 2302 Fibroscan*. HCV new positive rate was 21.3%. Our HCV active file was 651patients included these 24.8% new patients screened by DBS; 98% realized HCV genotype, HCV viral load and FIBROSCAN. DAA treatment was proposed to 96%; 95% started treatment, 4% were lost follow up or refused treatment. After treatment, there was 7 relapse and 3 reinfections by drug injection and cured rate of 94%. Sociological evaluation showed that 4 program qualities for patients: free access, closeness (outside hospital), speed (of the results) and availability (of nurse and social workers). Conclusions:  Specific follow-up of drugs users and other HCV high-risk patients including screening, early detection, diagnosis and treatment increase rate of treated and cured patients, with low rate of relapse and reinfections.
Keywords: Hepatitis C Virus (HCV); Drug Users; Cascade of Care; Outreach Screening; HCV Treatment